Evaluation of trace element levels in beef cuts available to the consumers in Serbia. Issue 1 (October 2021) - Djinovic-Stojanovic, J; Jankovic, S; Nikolic, D; Vranic, D
Abstract: The present study evaluated the levels of Mn, Se, Cu and Zn in beef cuts available at markets in Serbia. We also assessed the risk associated with the consumption of these foods based on the estimated daily intake (EDI) of these elements. Thirty-six beef meat cuts were analysed using inductively coupled plasma mass spectrometry (ICP-MS). The EDI of all the studied elements was estimated on the basis of a calculation of the amount of beef consumed by Serbian households (mean beef consumption of 17.2 g/person/day). The studied beef cuts pose no risk with respect to the EDIs of Mn, Se, Cu and Zn. Among the four studied beef cuts, shoulder had the highest content of dietary zinc (68.2 mg/kg).